Analisis Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Kebakaran Di RT.016/RW.04 Kelurahan Rawa Buaya Kota Jakarta Barat - Wahyu Nur Khasanah; Abdul Haris Fatgehipon; Nandi Kurniawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Fires in residential areas usually occur in densely populated areas. Rawa Buaya Village is a sub-district in West Jakarta City which has a fairly high population density and there is also a densely populated settlement located at RT.016/RW.04 with 445 families. This settlement experienced fire disasters five times in 2008, 2009, 2015, and twice in 2022. The aim of the research is to describe community preparedness to reduce the risk of fire as well as factors that support and inhibit community preparedness. This research uses descriptive methods through a qualitative approach. The results of the research show that 40% of the community knows that the cause of fires is due to human negligence, 81% have the desire to prevent fires, 76% have an agreement between the Head of the RT and the community, 74% have determined the evacuation location for victims, 67% do not know the evacuation route board, 91% have the desire to to help their relatives, 62% only knew that a fire simulation had been carried out once, 74% had no early warning system, and 60% had not prepared an emergency fund. So it was concluded that the community was sufficiently prepared to face fires by knowing the causes and things to prevent fires, having an agreement to prepare evacuation locations, helping relatives and participating in disaster simulations, but the vulnerability of the living environment was a factor that triggered fires.